Uso da impedância na determinação do volume globular das espécies felina, equina e bovina - Vieira, R. F.C.; Viol, M. A. [UNESP]; Barbosa, T. S. [UNESP]; Soeiro, C. S. [UNESP]; Bomfim, S. R.M. [UNESP]; Ciarlini, P. C. [UNESP] (My University, 2008)
The aim of this study was to determinate the correlation of packed cell volume (PCV) between cats, horses and cows with two different methods: by impedance and by the Strumia method. For this purpose, blood samples from 70 cats, 80 horses and 77 cows were analyzed. The PCV data, in both methods, were determined at 20 - 120 minutes after blood collection. The PCV data obtained by Strumia and impedance methods (r = 0.98 cats, r = 0.98 horses and r = 0.96 cows) were extremely significant (p < 0.0001) for the three species. In conclusion, the PCV data determined by impedance was reliable and it is recommended for clinical use in feline, equine and bovine species.
Impedance method for packed cell volume determination in feline, equine and bovine species
Keywords: Hematocrit; Impedance; Packed cell volume; Strumia